The Effect of Boron Fertilizer and Bokashi Dosage on Tomato Cultivation (Solanum lycopersicum) - Ferdinandus Tutu; M. Abror (CV. Media Digital Publikasi Indonesia, 2025)
This study aims to determine the effect of boron and bokashi fertilizer doses on the growth and yield of tomato plants (Solanum lycopersicum). Boron and bokashi fertilizers are two types of fertilizers that play an important role in increasing soil fertility and supporting plant growth. Boron plays a role in cell wall formation, flowering, and fertilization, while bokashi, as an organic fertilizer, can increase nutrient availability and improve soil structure. This study used a randomized block design (RBD) with two factors, namely boron fertilizer dosage (0, 1, 2, and 3 kg/ha) and bokashi dosage (0, 5, 10, and 15 tons/ha). The parameters observed included plant height, number of leaves, stem diameter, number of fruits, fruit weight, and sweetness. The results showed that boron fertilizer and bokashi treatments had a significant effect on most growth and yield parameters. A boron dose of 3 kg/ha produced the best results in terms of plant height and fruit weight, while a boron dose of 1 kg/ha produced the highest number of fruits. The application of a bokashi dose of 15 tons/ha also showed consistent results in improving vegetative growth and yield.